Stronghold, and Its Hinterland on the Basis of Klenica Settlement Complex, Lubuskie Voivodeship. A Summary of Studies to Date - Gruszka, Bartłomiej (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2022)
The early medieval fortified settlement in Klenica is located on the right bank of the Oder River, on the left side of the roadlea ding from Bojadła towards Klenica. The stronghold and its open suburb settlements boast a rich history of studies. The beginnings of archaeological excavations in the Klenica settlement complex date back to 1935, when Kurt Langenheim discovered the stronghold. Soon afterwards Ernst Petersen, the head of the State Office for Prehistory in Wrocław, commenced archaeological excavations by digging an 81-metre long trench, which allowed for the exploration of the southern stretch of the ramparts and the central part of the stronghold. In 2016 Andreas Kieseler carried out a study on archaeological material assembled in the pre-war period stored in the archives of the Museum of Archaeology in Wrocław. In a comprehensive study A. Kieseler also compiled the results of excavations carried out in 2007, which addressed some research questions and attempted to obtain samples for dendrochronology. The next stage was non-invasive research carried out in 2017. At that time geophysical studies using the magnetometry method in the area of the stronghold as well as a part of one of the suburb settlements were carried out. At that time many analyses on the reconstruction of the former natural environment were also conducted. One of the most interesting features discovered during geophysical research is an oval anomaly measuring 28×21 m, registered in the southern part of the stronghold. Results of magnetometry survey connected with the reinterpretation of the results of archaeological excavations allow us to put forward yet another research question concerning the function of these identified features. The results of dendrochronological dating allow us to conclude that the four-stage earth and wooden rampart had been constructed by 850 AD. The stronghold burnt down at the beginning of the 10th century and was not rebuilt afterwards.
il. ; 29 cm
Keywords: Klenica; stronghold; geophysical survey; early medieval settlement; Tornow-Klenica zone